Exploratory Review on Decision Support System for Disaster Management - Ka Hong S.G.; Ahmad A.; Raja Azman R.F.; Faudzi M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Decision making; Disaster prevention; Disasters; Human resource management; Industrial management; Catastrophic event; Decision support system (dss); Disaster management; Loss of life; Property damage; Search and rescue; Task complexity; Task management; Decision support systems